Il n'y a pas de cogito-femme - Collin, Françoise (L'émergence d'une culture au féminin, 1987)
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; cours; cycles supérieurs; discipline; fem1000; fem9000; histoire et politique; interdisciplinarité; philosophie; premier cycle; périodes historiques; québec; régions géographiques; sciences humaines; thématiques; études culturelles; études littéraires

Invisible Work - Daniels, Arlene Kaplan (Social Problems, 1987)
Our folk understanding of “work” focuses on those activities you “have to do” to get paid for them. Women's work is correspondingly devalued, for it is either unpaid or limited by the demands of the unpaid work in the home. This understanding also includes a moral force. One should contribute to society by working. This paper shows the restrictiveness of these commonsense understandings and discusses the kinds of work that consequently disappear from view. I focus especially on the work involved in the social construction of daily life and in the maintenance and development of institutions. Finally, I present the rationale for expanding the concept of work to include many activities not previously considered in the folk concept: a keener awareness of the work involved in social constructions serves to dignify the labor and engender respect for the workers who do it.
Keywords: discipline; histoire et politique; philosophie; projet charge mentale; sciences humaines; thématiques; travail; travail invisible

La dialectique de la reproduction - O'Brien, Mary (Les éditions du remue-ménage, 1987)
Dans La dialectique de la reproduction, essai de philosophie féministe, Mary O’Brien montre comment la pensée masculine et les institutions patriarcales ont été édifiées pour contrecarrer l’incertitude de la paternité et pour médiatiser l’exclusion des hommes du travail reproductif.
Keywords: 1900-1999; EDI; approches et analyses; care; corps; cours; discipline; division sexuelle du travail; fem1000; justice reproductive; philosophie; premier cycle; périodes historiques; sciences humaines; thématiques; travail du care